ANALYSIS TEORI HERZBERG TERHADAP KEPUASAN KERJA KARYAWAN UNIVERSITAS SANATA DHARMA YOGYAKARTA - Stefanus Rumangkit (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Motivation, employee performance, and employee work satisfaction are criteria that must befilled. Motivation in employee has an impact on working spirit to face the workplace. If the companydoes not support in giving motivation to employee so it can be ascertained that employeeperformance will decrease and it doesn’t create maximum employee work satisfaction.By applying of motivational and hygiene factor, makes the organization can retain itsemployees. This thing can lead an increasing of employees work satisfaction. The result of thisresearch indicates that a grow chance and recognition from others in theory motivational and worksatisfaction factor according to Herzberg is able to give positive impact on the employeeperformance.